Partners in Crime: Manipulating the Deferred Acceptance Algorithm through an Accomplice - Bendlin, Theodora; Hosseini, Hadi (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
We introduce a new manipulation strategy available to women in the men-proposing stable matching, called manipulation through an accomplice. In this strategy, a woman can team up with a potential male “accomplice” who manipulates on her behalf to obtain a better match for her. We investigate the stability of the matching obtained after this manipulation, provide an algorithm to compute such strategies, and show its benefit compared to single-woman manipulation strategies.